Ideologias, utopias e agir social segundo a Octogesima Adveniens - Alves, Antonio Aparecido (Revista Eclesiástica Brasileira, 2001)
Diante das grandes ideologias presentes e atuantes em seu tempo, que pretendiam responder plenamente ao anseio de unta vida verdadeiramente humana, Paulo VI propõe um outro caminho. Este artigo procura analisar a questão das ideologias na Octogesima Adveniens e as utopias, solução deixada por Paulo VI, relacionando-a com o agir social dos cristãos. Abstract: In face of the great ideologies present and active in his day that hoped to fully respond to the desires for a truly human life, Paul the 6h proposed anotherpath. This article attempts to analyse the question of the ideologies in the Octogesima Adveniens and the utopias, solution lelt by Paul the 6h, relating it to the social actions of Christians.